Working with AI: The Effect of Job Stress on Hotel Employees’ Work Engagement - Yong Hou; Liwei Fan (Behavioral Sciences)
Based on the Conservation of Resources (COR) theory and social support theory, this study focuses on the effects of AI-induced stress on hotel employees’ work engagement and examines the mediating role of psychological capital and the moderating role of perceived organizational support. A sample of five-star hotels in China was selected for the study, data were analyzed, and hypotheses were tested using SPSS 27.0 and Mplus 7.4 software. The results of the study revealed that AI-induced stress had a significant negative effect on work engagement and psychological capital mediated the relationship between AI-induced stress and work engagement. Perceived organizational support moderated the relationship between work stress and psychological capital. Specifically, the higher the perceived organizational support, the lower the negative effect of work stress on psychological capital; conversely, the lower the perceived organizational support, the higher the negative effect of work stress on psychological capital. The greater the negative impact of work stress on psychological capital, the higher the perceived organizational support, and the smaller the negative impact of work stress on psychological capital. The findings of the study not only enrich the research related to AI in the hotel industry but also have certain reference significance for managers in the hotel industry who introduce AI in managing their employees.